Sustainable Finance and Green Fintech - Ather Alam Khan,; Yasmeen Wahab, (Dialogue Social Science Review (DSSR), 2025)
Financial decision making which includes environmental, social and governance (ESG), is becoming more and more popular as a field called sustainable finance. At a time when the world is facing more and more climate risks, resource depletion and social inequalities, sustainable finance has become a very important means to generate economic resilience and environmentally responsible. Financial technology (fintech) is one of the most outstanding enablers of sustainable finance by utilizing digital innovation to increase access to green investment, transparency, and sustainable growth of the economy. In terms of the advancement of sustainable finance, fintech is at the forefront for the issuance of green bonds, allows ESG investing, and offers carbon footprint tracking tools, respectively. Blockchain, Big Data, Artificial Intelligence (AI) and Decentralized Finance (DeFi) help fintech find more ways for reallocation of capital to the more sustainable projects, while still maintaining efficient and accountable process. Blockchain based green bonds, AI driven ESG analytics as well as digital carbon credit markets are turning the table on FinTech to bring in sustainable investments as the easiest way, or perhaps, even more effective(Tang & Zhang, 2020). Focusing on fintech innovations, this is a study on how fintech innovations contribute to sustainable finance through green bond, ESG investment and carbon tracking mechanism impact. In this study, we explore the extent to which fintech can create the impact on income, health, technology, environment or social scale.Analysis by the authors finds the ability of fintech to create innovative online platforms for green investment, to enhance risk assessment model, etc., to significantly increase the pace of sustainability efforts. The main hurdles that the sector has to face, however, are regulatory uncertainty, cybersecurity concerns and a requirement for more standardization of ESG metrics. The contributions of this research to the scholarly conversations about sustainable finance augment the academic discussion on the regulatory framework and the sustainable investment models, which financial institutions, policymakers and fintech innovators may look into in facilitating the adequate formation of more effective regulatory framework and sustainable invest models. This study discusses the contribution of fintech to sustainable finance by emphasizing on future potential for using technology for solving global sustainability challenges.